2017
DOI: 10.1108/sampj-04-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social and environmental reporting practices

Abstract: Purpose The purpose of this paper is to explore corporate social and environmental reporting (CSER) practices and motivations in Bangladesh. Design/methodology/approach Using a mixed-methods approach, the paper attempts to understand what corporate social and environmental issues Bangladeshi firms are reporting and why. The paper first explores the motivations for CSER in line with O’Dwyer’s (2003) proposed classifications of proactive and reactive motivations through interviews and frames its findings using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 106 publications
5
33
0
Order By: Relevance
“…Researchers also used a mixed approach in the past in the reporting analysis. Hossain et al [54] and Nurunnabi [6] used interview and content techniques for environmental reporting. Moreover, in the content analysis techniques, general disclosure of content is mostly used in sustainability reporting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers also used a mixed approach in the past in the reporting analysis. Hossain et al [54] and Nurunnabi [6] used interview and content techniques for environmental reporting. Moreover, in the content analysis techniques, general disclosure of content is mostly used in sustainability reporting.…”
Section: Methodsmentioning
confidence: 99%
“…Green reporting practices have been increasing in developing countries such as Bangladesh in the last few years. Prior research studies outlined that the absence of specific guidelines, weaker stakeholder engagement, and lack of social awareness are reasons for poor green reporting performance in Bangladesh [6,54,55]. Hossain et al [21] reveal that Bangladeshi banking companies' green disclosure level is poor even though it has improved since 2011 due to the initiatives of the central bank green guidelines.…”
Section: Bb's Green Regulationmentioning
confidence: 99%
“…In practice, however, several studies have revealed the existence of information deficiencies (Asif, Searcy, dos Santos, & Kensah, 2013;Mio, 2010;Moseñe, Burritt, Sanagustín, Moneva, & Tingey-Holyoak, 2013;Rodrigue, 2014) that hinder decision-making by the different stakeholders (Fonseca, McAllister, & Fitzpatrick, 2012;O'Dwyer, Unerman, & Hession, 2005). Among other weaknesses, the fact that the information disclosed is minimal, of limited effectiveness and credibility, and rarely comparable, all limits corporate transparency (Amini, Bienstock, & Narcum, 2018;Boiral & Henri, 2017; Cubilla-Montilla, Nieto-Librero, Galindo-Villardón, Vicente Galindo, & Garcia-Sanchez, 2019;Hossain, Momin, Rowe, & Quaddus, 2017;Mio, 2010). In addition, it has been empirically demonstrated that the relevance of the NFI disclosed is associated with the existence of firms' incentives.…”
Section: Introductionmentioning
confidence: 99%
“…Hossain et al [48] have approached corporate social and environmental reporting (CSER) practices and motivations in Bangladesh. They found that community investment and development and governance codes and policies categories received the highest amount of disclosure, while the least disclosed was the workplace/human rights category.…”
Section: Literature Reviewmentioning
confidence: 99%